1990
DOI: 10.1210/jcem-71-2-533
|View full text |Cite
|
Sign up to set email alerts
|

An Inhibitory Insulin-Like Growth Factor Binding Protein (In-Igfbp) From Human Prostatic Cell Conditioned Medium Reveals N-Terminal Sequence Identity With Bone Derived in-Igfbp

Abstract: Insulin-like growth factor binding proteins (IGFBPs), are produced by several cell types, are present in biological fluids, and may function in modulating insulin-like growth factor (IGF) biological activities. Recently the presence of multiple IGFBPs was reported in seminal fluid, suggesting that IGFBPs are produced by prostatic epithelium. We have found that human prostatic tumor cells of the PC3 cell line produce an IGFBP. PC3-IGFBP was purified to homogeneity using sequential IGF I affinity and HPLC C4 rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…The role of IGFBP-3 as a growth-inhibitory protein has been previously demonstrated by us and others in various cell types (9,(12)(13)(14)(15)(16)(17). Initially, IGFBP-3 was thought to inhibit growth by binding to IGFs and sequestering them from their receptor.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The role of IGFBP-3 as a growth-inhibitory protein has been previously demonstrated by us and others in various cell types (9,(12)(13)(14)(15)(16)(17). Initially, IGFBP-3 was thought to inhibit growth by binding to IGFs and sequestering them from their receptor.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to regulating the availability of free IGFs and, therefore, their mitogenic activity (1)(2)(3)(4), IGFBPs also play an important role in directly regulating cell growth. These independent cell growthregulatory effects of IGFBPs have been shown to be either growth-inducing (5-10), or growth-inhibiting (9,(12)(13)(14)(15)(16)(17).…”
Section: Insulin-like Growth Factor (Igf) Binding Protein-3 (Igfbp-3)mentioning
confidence: 99%
“…In vitro studies have demonstrated that several components of the IGF1 system are involved in the regulation of the growth of prostate-derived cells (Perkel et al 1990, Cohen et al 1991, 1994a. In primary culture, the prostatic epithelial cells express the IGF1 receptor and IGF1 stimulates them to proliferate and to produce IGFBPs into the medium (Perkel et al 1990, Cohen et al 1991.…”
Section: Introductionmentioning
confidence: 99%
“…In primary culture, the prostatic epithelial cells express the IGF1 receptor and IGF1 stimulates them to proliferate and to produce IGFBPs into the medium (Perkel et al 1990, Cohen et al 1991. Prostatic stromal cells also express the IGF1 receptor (Cohen et al 1994a,b,c), and there is local production of IGF1 in these cells (Kaplan et al 1999, Meinbach & Lokeshwar 2006.…”
Section: Introductionmentioning
confidence: 99%
“…It is secreted by a number of different cell types in vitro and IGFBP-4 mRNA is expressed in a variety of tissues (6,7,(22)(23)(24)(25)(26)(27)(28)(29). Although its precise biological function is unknown, IGFBP-4 has been implicated as a potent inhibitor ofIGF action in bone and in other systems (8,22,26,(30)(31)(32). Recently, we reported that, in contrast to an increase in IGFBP-3, treatment of normal human fibroblasts and human osteoblast-like cells with IGF-I or IGF-II led to a marked reduction in the levels of 24-kD IGFBP-4 detected in the cell-conditioned medium (25,33).…”
Section: Introductionmentioning
confidence: 99%